Association between resilience and frailty among Chinese older adults - Wang, Yujie; Chen, Yingwei; Xu, Jixiang; Chen, Hao; Gao, Junling (Frontiers in Psychiatry, 2022)
Purpose: Resilience is a multidimensional concept determining healthy aging, however, there were limited studies examining the association between frailty and resilience in detail. In this study, we aimed to examine the association of frailty with three dimensions of resilience-strength, optimism, and tenacity among Chinese older adults. Methods: A cross-sectional study was conducted among 10,209 participants who were sampled by three-stage sampling method, from three cities in China from June 2020 to July 2021. The Chinese version of the Connor–Davidson Resilience Scale (CD-RISC) was used to measure resilience’s 3 dimensions (strength, optimism and tenacity), which were converted into quartiles for the analysis. Frailty status was measured using the Chinese version of the FRAIL scale, categorized into robustness, pre-frailty and frailty. Multinomial logistic regression was used to examine associations between frailty status with strength, optimism and tenacity. Results: The overall proportions of robustness, pre-frailty, and frailty were 42.7%, 48.7%, and 8.6%, respectively. After controlling for sociodemographic characteristics, self-rated health, and health behaviors, compared with older adults with the lowest quartile of strength, older adults with the second quartile (odds ratio, OR = 0.67, 95% CI: 0.57−0.78), third quartile (OR = 0.60, 95% CI: 0.50−0.72), and fourth quartile (OR = 0.58, 95% CI: 0.46−0.73) of strength had lower ORs for pre-frailty, and who also had lower ORs(0.44, 95% CI: 0.33−0.58; 0.42, 95% CI: 0.30−0.59; 0.34, 95% CI: 0.20−0.56, respectively) for frailty. There were no homogeneous associations between optimism and tenacity with frailty status. Conclusion: Higher strength was associated with lower chance of being pre-frail and frail among Chinese older adults. This finding implies that community-based training programs aiming to enhance psychological resilience, especially strength, may contribute to healthy aging. Future studies should examine the effects of resilience on frailty using longitudinal or experimental study designs in cross-cultural contexts.